Xanthomonas natriuretic peptide is recognized by the Arabidopsis natriuretic peptide receptor 1 and through this interaction triggers similar plant responses to its plant counterpart. (January 2023) - Di Paolo, Valeria; Masotti, Fiorella; Vranych, Cecilia V.; Grandellis, Carolina; Garavaglia, Betiana S.; Gottig, Natalia; Ottado, Jorgelina
Abstract: Plant natriuretic peptides (PNPs) are hormone peptides that participate in the regulation of ions and water homeostasis in plants. Xanthomonas citri subsp. citri (Xcc) the causal agent of citrus canker disease also possesses a PNP-like peptide (XacPNP). This peptide, similarly to AtPNP-A, the most studied PNP from Arabidopsis thaliana, causes stomatal aperture and enhances photosynthetic efficiency in plant leaves. Thus, the function that has been attributed to XacPNP is to contribute to maintain photosynthetic efficiency and water homeostasis in plant tissue during the infection process, to create favorable conditions for biotrophic pathogens survival. A PNP receptor (AtPNP-R1) for AtPNP-A has been identified and the AtPNP-A activity in regulation of water homeostasis has been observed to depend on the presence of AtPNP-R1. Here, we demonstrated that both AtPNP-A and XacPNP require the presence of AtPNP-R1 to induce plant stomatal aperture. Also, less necrotic tissue was found in infections with pathogens expressing XacPNP and this was dependent on the presence of AtPNP-R1, suggesting that XacPNP interacts with this receptor to exert its function. Finally, we confirmed that AtPNP-A and XacPNP interact with AtPNP-R1 in planta, which support the idea that XacPNP triggers similar plant responses to its plant counterpart. Graphical Abstract: ga1 Highlights: Bacterial natriuretic peptide XacPNP and the Arabipdosis PNP AtPNP-A. requires AtPNP-R1 receptor to open stomata. Healthier tissue conditions found in plants infected with pathogen bearing. XacPNP depends on the presence of AtPNP-R1. XacPNP as well as AtPNP-A interact with AtPNP-R1 in planta.